1998
DOI: 10.1557/jmr.1998.0226
|View full text |Cite
|
Sign up to set email alerts
|

Niobium-titanium oxide powders obtained by laser-induced synthesis: Microstructure and structure evolution from diffraction data

Abstract: The influence of the niobium content on the anatase-to-rutile phase transition in nanopowders of Nb–Ti oxides was studied and the changes in the particle size and microstrain distribution obtained at different temperatures were analyzed. A correlation is found between the initial microstructure in the Ti1 – xNbxO2 (x = 0.03, 0.2) powder and the niobium content. The presence of Nb was found to inhibit the growth of both the anatase and the rutile phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…3͒. The ratio between anatase and rutile extracted from XRD spectra was computed with the empirical relationship used by Depero et al 19 R͑T ͒ϭ0.679…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3͒. The ratio between anatase and rutile extracted from XRD spectra was computed with the empirical relationship used by Depero et al 19 R͑T ͒ϭ0.679…”
Section: Resultsmentioning
confidence: 99%
“…12-14 The effect of Nb doping in titania and its importance for oxygen sensors has recently been highlighted by several articles, [15][16][17][18][19] indicating higher device sensitivity 20 at lower working temperatures. 21,22 Likewise, recent studies have shown the feasibility of using Nb/TiO 2 as surface conductance CO sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31] The percentage of rutile is estimated as 93.1 and 52.4 % for Nb:TiO 2 -01 and Nb:TiO 2 -20 samples, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…TiNb 2 O 7 can be synthesized by a variety of processes such as solid state synthesis [6], laser-induced pyrolysis [7], hydrothermal crystallization [8], and evaporation-induced self-assembly (EISA) [1].…”
Section: Introductionmentioning
confidence: 99%